Prarancangan Pabrik N-Methylaniline Kapasitas 35.000 Ton/Tahun - Atmaja, Fajar Putra, Ir. Haryanto AR., M.S, Dr. Ir. Ahmad M Fuadi, M.T (2016)
N-methylaniline factory with raw materials chlorobenzene and methylamine which has a capacity of 35,000 tons / year is planned to operate for 330 days / year. The process of making n-methylaniline carried out in a stirred tank flow reactor equipped with a heating coil. In the reactor the reaction at liquid-liquid phase, irreversible, endothermic with isothermal conditions at a temperature of 215oC and at a pressure of 68 atm. This plant is classified at high risk because of the operating conditions at a pressure of 68 atm Methylamine raw material requirements of 1103.404 kg/hr and chlorobenzene amounted to 3989.912 kg/hour. Supporting materials NaOH 50% at 1406.811 kg/h and needs a catalyst 1547.59 kg/hour. Products such as n-methylaniline amounted to 4419.192 kg/hour. Support utilities includes supplying process water extracted from the river of 9730.9745 kg/hour and the supply of saturated steam at 3655.2724 kg/hour obtained from the boiler with diesel fuel amounted to 965.8 liters/hour, demand for electricity is obtained from the PLN and generator set of 8,000 kW as fuel reserves 796.39 kg/hour. The factory was established industrial region, Gresik, East Java, with a land area of 30,000 m2 and total number of employees 160 people. Factory n-methylaniline established require a fixed capital of Rp.767.364.832.305 and working capital of Rp 186 139 805 917. From the economic analysis of this plant demonstrates a pretax profit Rp.346.347.211.207 / year after tax 30% profit reached Rp 242 443 047 845 / year. Percent Return On Investment (ROI) before tax after tax 45.13% and 31.59%. Pay Out Time (POT) before tax for the year of 1.81 and 2.4 years after tax. Break Even Time (BEP) amounted to 44.59%, and Shut Down Point (SDP) amounted to 26.26%. Discounted Cash Flow (DCF) accounted for 38.7%. From the data above feasibility analysis concluded that the plant is profitable and feasible to set.